Pemaknaan Kembali Eksistensi Akuntansi Syariah: Kajian Epistemologi - Agus Munandar; Dini Marina (Kompartemen : Jurnal Ilmiah Akuntansi, 2018)
ABSTRACTThe Purpose of this study is to perform reinterpretation existence of sharia accounting based on epistemology approach. Based on diversed opinions whether accounting is science or art, this article stated that sharia accounting is science. This statement proved using the conceptual framework developed some islamic scholars and philosopher such as truth theory and espitemology approach. Finally, this article proposes that sharia accounting have some legitimacy as a subject of study.Keywords: legitimacy, science, sharia accounting